Uso de antibacterianos en infecciones del tracto respiratorio inferior, en el Centro Médico Naval, año 2002 - Mendoza L., Jannelle C. (2004)
The present research was developed in the Centro Médico Naval «Cirujano Mayor Santiago Távara», considering 206 clinical histories of patients hospitalized with antibacterial treatment during the period January-December of 2002, in the Services of: Pediatrics, Internal Medicine, Pneumology and Geriatrics. Whose general objective was to evaluate the antibacterial therapy in the infections of the inferior respiratory tract in order to determine the effectiveness of the antibacterial usage in patients.Of the analyzed histories; 33% repayed to acute exacerbation of bronchitis (AEB), 53% to community-acquired pneumonia(CAP) and 14% to infectious exacerbation of the bronchiectasias (IEB), most of the patients presented common symptoms as cough 84%, high production of sputum 67% and fever 65%.The antibacterial drugs prescribed with more frequently were cefuroxime 36%, ciprofloxacin 15% and claritromycin 15%.The antibacterial treatment prescribed for the patients was a monotherapy with cefuroxime 44%, claritromycin 17% and ceftriaxon 13%; and as a associate therapy ceftriaxon/ciprofloxacin 8%, cefuroxime/claritromycin 7%, cefuroxime/ ciprofloxacin 7%.In conclusion, the antibacterial drugs used was effective because changes didn't exist in the initial therapy. However, in the cases in which changes were made in the initial therapy 27%, the justification was not reported in 58% of cases.